Strategi Perawatan Bahan Perpustakaan Di Dinas Perpustakaan Dan Kearsipan Kota Solok - Budiman Muslim (THE LIGHT : Journal of Librarianship and Information Science, 2021)
The library is an institution that has an important role in collecting and preserving information sources. These sources of information need to be preserved to maintain their physical form and the content of information they contain. Therefore, it is necessary to carry out activities for the preservation of library materials that are sustainable and in accordance with the provisions. The research was conducted qualitatively by utilizing secondary data sources obtained from official publications of agencies and institutions, applicable laws and regulations, and other related publications. Actions for maintaining library materials that can be taken are exterminating insects, removing stains and tape, and cleaning dust.